Velocity Concepts: A Reply - Lounsbury, Raymond H. (Quarterly Journal of Economics, 1932)
Journal Article Velocity Concepts: A Reply Get access Raymond H. Lounsbury Raymond H. Lounsbury University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 3, May 1932, Pages 569–574, https://doi.org/10.2307/1883404 Published: 01 May 1932